Deforestation in the MERCOSUR Countries: A comparative analysis of trends, policies, and governance (2000–2024) - Piñeiro, Valeria; Papendieck, Sabine; Elverdin, Pablo; Illescas, Nelson; Jorge, Nicolás; Mingoti, Rafael; da Silveira, Hilton Luis Ferraz; Campos, Silvia Kanadani; da Pereira, Vanessa da Fonseca (International Food Policy Research Institute, 2025)
The countries of MERCOSUR—Argentina, Brazil, Paraguay, and Uruguay (ABPU)—are home to some of South America's most vital and diverse forest ecosystems. These include the globally significant Amazon rainforest, the biodiversity-rich Cerrado savannah, and the expansive and carbon-dense Gran Chaco dry forests. Together, these ecosystems regulate hydrological cycles, support endemic biodiversity, store vast amounts of carbon, and provide critical ecosystem services to rural and urban populations alike.